History Curricula from Around the World for the 21st Century. Issue 1 (1st December 2001) - Nichol, Jon; O'connell, Kevin
History curricula from around the world are extremely varied yet share many common features. A central concern is education for citizenship, both in terms of national identity and the development of the values, attitudes, knowledge and understanding and thinking skills to participate. History curricula actively respond to the particular circumstances of the countries concerned, particularly where society is in a rapid state of transition and faces serious challenges and problems.